Determinants of maternal care utilization among young Muslim women in India. - Saradiya Mukherjee,; Rakesh Chandra, (Universiti Kebangsaan Malaysia, 2014)
Indian Muslims, compared to their counterparts from other religions, lag behind on several yardsticks related to socioeconomic progress and the same is true with maternal health care utilization. Due to low age at marriage among Muslims, a majority of births is ascribed to young (15-24 years) mothers, which pose serious concerns on the maternal health care of Young Married Muslim women (YMMW). A thorough search of past literatures on Muslim women’s maternal health care reveals that the research on the determinants of maternal health care utilization among Muslim women is almost absent.Retrieving data from the National Family Health Survey -3 (2005-06) this study attempts to assess the level of utilization and factors effecting three key maternal health indicators [Full Antenatal Care (ANC), safe delivery and Postnatal Care (PNC)] among YMMW (15-24 years) in India. Bi-variate analysis and chi-square test was applied and variables which were found to be significant were further included in binary logistic regression.The findings of the study reveal abysmally low levels of utilization for all three indicators of maternal health care i.e. full ANC, safe delivery and PNC. Multivariate analysis reveals that no mass media exposure, lower autonomy,education, poor economic background, higher birth order and unintended pregnancy are some of the reasons behind low maternal health care utilization.The study suggests educating Muslim girls, promoting family planning use,involving media and collaboration between religious leader and health care system could be some important policy level interventions to address the unmet need of maternity services among YMMW. Existing government policies and programs should integrate YMMW who are poor and belong to backward states with poor demographic indicators.